Konsep Pengelolaan Air Dalam Islam - Zahra Zainun Nisa (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2017)
Water is a long-life necessity that must be maintained for its sustainability. However, at present, various water resources problems have occurred in various countries. This study aims to find the concept of water resources management in Islam. This research type is library research with constant comparative method for data analysis. From the analysis, it can be understood that, Islam as a complete religion can be a source of water resource management concept to be implemented in life. For the sake of good water resources, water management must be holistic. An ethical-religious, social and economic approach that involving all human components is really essential.